Evaluation of the health risks related to the presence of cyanogenic glycosides in foods other than raw apricot kernels. (11th April 2019) - ,; Schrenk, Dieter; Bignami, Margherita; Bodin, Laurent; Chipman, James Kevin; del Mazo, Jesús; Grasl‐Kraupp, Bettina; Hogstrand, Christer; Hoogenboom, Laurentius (Ron); Leblanc, Jean‐Charles; Nebbia, Carlo Stefano; Nielsen, Elsa; et al.
Abstract: In 2016, the EFSA Panel on Contaminants in the Food Chain (CONTAM) published a scientific opinion on the acute health risks related to the presence of cyanogenic glycosides (CNGs) in raw apricot kernels in which an acute reference dose (ARfD) of 20 μg/kg body weight (bw) was established for cyanide (CN). In the present opinion, the CONTAM Panel concluded that this ARfD is applicable for acute effects of CN regardless the dietary source. To account for differences in cyanide bioavailability after ingestion of certain food items, specific factors were used. Estimated mean acute dietary exposures to cyanide from foods containing CNGs did not exceed the ARfD in any age group. At the 95th percentile, the ARfD was exceeded up to about 2.5‐fold in some surveys for children and adolescent age groups. The main contributors to exposures were biscuits, juice or nectar and pastries and cakes that could potentially contain CNGs. Taking into account the conservatism in the exposure assessment and in derivation of the ARfD, it is unlikely that this estimated exceedance would result in adverse effects. The limited data from animal and human studies do not allow the derivation of a chronic health‐based guidance value (HBGV) for cyanide, and thus, chronic risks could not be assessed. Abstract : This publication is linked to the following EFSA Supporting Publications article: http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2019.EN-1601/full